BUSINESS PROCESS IMPROVEMENT MODEL FOR THE SEVENTH-DAY ADVENTISTS TERTIARY INSTITUTIONS IN SOUTHERN ASIA PACIFIC REGION - Rantung, Danny Ivan (JIU (Jurnal Ilmiah Unklab); Volume 5 No. 1, 2002 JIU UNKLAB, 2002)
In the world of academe, business Process Improvement (BPI) is seen as one of the leading methodologies to deliver higher educational institutions with high quality products and services. The main objective of BPI is to improve business processes, and hence its approach is to address business and production processes, not people, as the means of improvement. This research surveyed the existing operating and administrative system and procedures of the tertiary institutions of the Seventh-day Adventists in Asia Pacific Region and on this basis, proposed a BPI model that could be adopted by said schools. The study yielded following results: (1) The Seventh day Adventist tertiary institutions in the Southern Asia Pacific Region are ready for BPI. However, certain dimensions of the existing culture may impede readiness for BPI. These include a bureaucratic structure that requires everyone to stick to formal structures and procedures and low risk tolerance where there is pressure to make the right decisions. (2) The existing operating and administrative system and procedures of the Seventh-day Adventists Tertiary Institutions in Southern Asia Pacific Division may serve the present needs of the institutions but need to be redesigned to achieve world-class performance. This is the purpose of the proposed BPI change initiative using the model proposed by the researcher. (3) The Seventh-day Adventists Tertiary Institutions in Southern Asia Pacific Division are beset with serious problems relating to processes concerning human resource management, inventory control and school plant management. The proposed BPI model provides a guide to the tertiary institutions for a change initiative. It contains both analytical and “normative” elements. Its analytical features dissect and clarify problems; the normative part synthesizes solutions, utilizing design principles applied to findings from analyzing existing operating and administrative systems and procedures of the institutions. The normative and analytical components are thus linked, and together constitute an integrated management change model.